Modifications of atrial natriuretic peptide and vasopressin peptides in the rat hypothalamic supraoptic nucleus during resistance training - Farina Lipari, Elvira; Lipari, Diego; Valentino, Biagio (Italian Journal of Anatomy and Embryology, 2010)
Many studies have demonstrated the involvement of atrial natriuretic peptide (ANP) and vasopressin (VP) in the homeostasis of body fluids, but few studies have regarded the hypothalamic magnocellular neurosecretory system during physical exercises. The aim of the present immunohistochemical work is to study the activity of ANP and VP secreting neurons of the hypothalamic supraoptic nucleus during and after resistance training. The study was carried out in Wistar rats trained by a physical resistance-type exercise, using a rung ladder and a varying load fastened to the tail of each rat; the exercise lasted 20 min everyday for periods of 15, 30 and 45 days. Animal groups were sacrificed at the end of each training period and one group was sacrificed after 60 days from the beginning of training, i.e.15 days after completing a 45 day training. The results show that ANP and VP-immunopositivity is at first lesser in the trained rats than in the corresponding controls and then increases from the 15th to the 45th day of training; the increase of the immunopositivity in the trained rats indicates a decreased degranulation of the neurons. The comparison between VP and ANP-immunopositivity suggests that in the early phase of training VP-release in the bloodstream is higher than ANP-release, therefore the antidiuretic action of VP is expected to prevail on ANP action and an electrolyte unbalance may occur.